Cognitive profile of patients with glycogen storage disease type III: a clinical description of seven cases. Issue 3 (12th November 2014) - Michon, Claire‐Cécile; Gargiulo, Marcela; Hahn‐Barma, Valérie; Petit, François; Nadaj‐Pakleza, Aleksandra; Herson, Ariane; Eymard, Bruno; Labrune, Philippe; Laforet, Pascal
Abstract: Background: Glycogen storage disease type III (GSDIII) is a rare autosomal recessive disorder due to glycogen debranching enzyme (GDE) deficiency. It results in a multisystemic disease with predominant hepatic and myopathic symptoms. While frequent social maladjustment has been observed in our clinical practice, cognitive and psychological disturbances have never been assessed. The aim of this pilot study was to examine and characterize the cognitive profile of patients with GSDIII. Methods: Seven patients (six women and one man, mean age: 38.7 ± 11.6 years) with GSDIII underwent a neuropsychological set of tests assessing global cognitive efficiency, executive functions, social cognition, apathy, and episodic memory. Results: All patients presented previous psychopathological history. We observed attention fluctuations for each patient, and impaired global cognitive efficiency with deficiencies in executive functions in 5/7 patients. Emotional skills (social cognition) were impaired in five patients. Memory was mostly preserved. Conclusion: The impairment in social cognition (recognition of emotions and ability to attribute mental states to others) and executive functions observed could be a consequence of orbito‐frontal dysfunction due to the abnormal glycogen metabolism characteristic of the underlying disease. These results are consistent with the hypothesis of a central nervous system involvement in patients with GSDIII, but need to be confirmed in future research. This could explain the social and economic difficulties, and the lack of compliance to the medical follow‐up presented by these patients. It suggests that these disturbances need to be taken into account when planning the medical management of patients with GSDIII.